(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors describe the morphology of male genitalia of the species present in Italy and belonging to Thoracobombus subgenus putting on, for the various parts of these structures, the aspects to be considered for diagnostic purposes. The elements of greater discriminating power have been employed in order to compile a dichotomic key of the species of this subgenus.